EFEKTIVITAS MINUM AIR PUTIH DENGAN BACAAN SURAT AL-FATIHAH UNTUK MENURUNKAN KANTUK DI DALAM KELAS - Zumailah (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2023)
This study aims to determine the effectiveness of drinking water with the recitation of surat al-fatihah to reduce sleepiness in the classroom. The method used is quasi experimental method with the design